Attitudes and Intentions of Business Master Students towards Sustainable Tourism and Entrepreneurship - Alina Badulescu; Daniel Badulescu; Dorin Bac; Sebastian Sipos-Gug (Amfiteatru Economic Journal, 2014)
Sustainable development has become in the last three decades an issue of high importance, both from theoretical view and from the public policies' view. Nevertheless, sustainable development can be generated only by sustainable enterprises and businesses, which should take into consideration not only the economic aspects, but also the social and environmental ones, i.e. businesses striving to meet the ”triple bottom line”. This paper aims at investigating master students in Business Administration, i.e. future business people, are actually prepared for creating and running businesses in sustainable tourism and which is the profile of future “sustainable entrepreneur”. In order to answer this question, a surveybased research was conducted among master students in Business administration, concerning aspects such as: what is the understanding of business master students on ”sustainability” issues and which are their sustainability-related habits, attitudes and behaviour as consumers. We used factorial analysis, resulting in a four factors model, to investigate attitudes related to: importance to run a sustainable business, the use of renewable energy resources, recycling used products, employing local labour force, promoting the use of local resources etc. The paper presents the main findings in the context of previous researches in the literature, drawing conclusions and proper recommendations.
Keywords: L26; Q56; A23; A29; L83; 330; attitudes toward sustainable tourism and entrepreneurship; entrepreneurial